Alternating bio‐based pyridinic copolymers modified with hydrophilic and hydrophobic spacers as sorbents of aromatic pollutants. (14th December 2021) - Jlalia, Ibtissem; Chabbah, Taha; Chatti, Saber; Schiets, Frédéric; Casabianca, Hervé; Marestin, Catherine; Mercier, Regis; Weidner, Steffen M.; Kricheldorf, Hans R.; Errachid, Abdelhamid; Vulliet, Emmanuelle; Hammami, Mohamed; et al.
Abstract: The main objective of this work was to design new advanced sorbent phases, alternating copolymers, derived from isosorbide and 2, 6‐difluorpyridine, to be used for the removal of aromatic organic pollutants present in water at low concentrations. Six different monomers, dianhydrohexitols isomers and bisphenol derivatives, were synthesized in order to make it possible to study their hydrophilic and hydrophobic effect on the sorption efficiency of the resulting polymeric phases. Before this study, we have confirmed the chemicals structures, molecular weights, and thermal properties of the obtained polymeric phases. Sorption results show a higher adsorption efficiency of P6 co‐poly(ether‐pyridine) based on bisphenol substituted with pyridine units, for all tested pollutants, hydrophobic and hydrophilic ones, due to its less compact structure. Two aromatic organic pollutants, p‐hydroxybenzoic acid and toluic acid, were selected as sorbates to study the adsorption characteristic, kinetics and isotherms of the co‐poly(ether pyridine) P6. Langmuir model led to a better fitting of the sorption isotherms; the sorption of toluic acid is easier than of that p‐hydroxybenzoic acid. Comparing 1/n values for benzoic acid was two time lower for P6 compared to that for biochar and for cross‐linked methacrylate resin, showing a higher efficiency.